Strengthening the development impact of UNCTAD's investment policy reviews - Jungnickel, Rolf,Koopmann, Georg (online, 2005)
Abstract:
urn:nbn:de:0168-ssoar-117136
Keywords: (stw)Auslandsinvestition; (stw)Investitionspolitik; (stw)Entwicklung; (stw)Welt; (stw)Entwicklungsländer; (thesoz)Entwicklungspolitik; (thesoz)Investitionspolitik; (thesoz)Direktinvestition; (thesoz)UNCTAD; (thesoz)Auslandsinvestition; Graue Literatur; Gutachten; Auslandsinvestition; Investitionslenkung; Staatliche Investitionspolitik; Entwicklung